Ketidaksinambungan Litologi dan Karakteristik Pedogenetik pada Beberapa Andisols di Jawa Barat - Rina Devnita; Mahfud Arifin; Ridha Hudaya; Apong Sandrawati; Ade Setiawan (Soilrens, 2018)
ABSTRACT Andisols developed from parent materials of volcanic eruptions. Volcanic eruptions can occur within several periods, resulting in a sequence of soil layers that can differ from each period and produced lithologic discontinuity in the soil profile. Lithologicac discontinuity was investigated in Andisols developed from the eruptions of Mt. Tangkuban Parahu (Holocene, andesitic) and Mt. Tilu (Pleistocene, basaltic) in West Java through morphological observations of three profiles at each location. The results showed that there was lithologic discontinuity in all profiles indicated by changed in color by Munsell Soil Colour Chart, organic carbon, texture and structure as the specific A buried horizon that developed from the parent material of the earlier eruption period than the horizons above. It is recommended to carry out the mineralogical and micromorphological analyses to determine the differences in minerals and micromorphology of the discontinue horizons and carbon-dating analysis in the buried layer to determine the age of the soil and the period of eruption that developed the soil.Keywords: A buried horizon, Munsell Soil Colour Chart, organic carbon, soil mineralogy, soil morphology